2016
DOI: 10.18632/oncotarget.10050
|View full text |Cite
|
Sign up to set email alerts
|

Activation of volume-sensitive Cl− channel mediates autophagy-related cell death in myocardial ischaemia/reperfusion injury

Abstract: Excessive reactive oxygen species (ROS) plays an important role in myocardial ischemia/reperfusion (I/R) injury, which triggers not only myocardial cellular apoptosis but also autophagy-related cell death, in which volume-sensitive outwardly rectifying (VSOR) Cl− channel-activated by ROS contributes to cell apoptotic volume decrease, playing an incipient incident of cellular apoptosis. However, whether VSOR Cl− channel concurrently participates in autophagy-related cell death regulation remains unclear. To ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
2
21
1
Order By: Relevance
“…We also found that administration of 3‐MA alone reduced myocardial infarct size versus control, a result similar to that obtained by Xia et al . () but opposite to the report from Ling et al . (), who used 50 times our dose.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We also found that administration of 3‐MA alone reduced myocardial infarct size versus control, a result similar to that obtained by Xia et al . () but opposite to the report from Ling et al . (), who used 50 times our dose.…”
Section: Discussioncontrasting
confidence: 94%
“…(Korkmaz et al, ) that acts via the MEK/ERK pathway (Pattingre et al, ) and 3‐Methyladenine (3‐MA, 0.3 mg·kg −1 b.w. ; Xia et al, ), also well known as a class I and III inhibitor of PI‐3K that inhibits autophagy (Wu et al, ) as shown in Figure A. We found that addition of U0126 slightly reduced myocardial infarct (MI) size, while 3‐MA infusion decreased MI as compared to control Figure B–E.…”
Section: Resultssupporting
confidence: 51%
“…4, type B mechanism). Swelling-independent, H 2 O 2 -induced activation of VSOR was originally found independently in 2004 by three groups (Browe and Baumgarten, 2004;Shimizu et al, 2004;Varela et al, 2004) and was confirmed by subsequent studies (Wang et al, 2005;Jiao et al, 2006;Varela et al, 2007;Harrigan et al, 2008;Liu et al, 2009;Deng et al, 2010a,b;Crutzen et al, 2012;Holm et al, 2013;Shen et al, 2014;Xia et al, 2016;Wang et al, 2017a,b). In addition, for the first time, VSOR per se was identified as the anion channel responsible for the Cl 2 efflux causing apoptotic cell shrinkage, called AVD , which was observed after stimulation with an intrinsic mitochondrion-mediated apoptosis inducer (staurosporine) due to increased ROS production via NAD(P)H oxidase (NOX) (Fig.…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 67%
“…Several lines of evidence have demonstrated that LAMP2 deficiency leads to the accumulation of CE in the cells, through which it will induce the formation of foam cells in the case of macrophages [10,11]. Moreover, LAMP2, which is a major player in autophagy process, has been upregulated in ischemic and inflammatory conditions [16,17,25]. It has been hypothesized that enhancement of autophagy could have a protective effect in aforementioned conditions.…”
Section: Primer Forward Reversementioning
confidence: 99%
“…LAMP2 mutation is the main cause of Danon disease, which with its typical characteristics include cardiomyopathy along with skeletal myopathy and mental retardation [15]. Several lines of evidence have demonstrated altered expression of autophagy-associated proteins including LAMP2 in inflammatory conditions [16,17]. Since CAD is considered an inflammatory disease, it is expected, that circulating levels of LAMP2 might be associated with pathogenesis of CAD.…”
Section: Introductionmentioning
confidence: 99%